2018
DOI: 10.1007/s10936-018-9601-8
|View full text |Cite
|
Sign up to set email alerts
|

Core Semantic Links or Lexical Associations: Assessing the Nature of Responses in Word Association Tasks

Abstract: The processes tapped by the widely-used word association (WA) paradigm remain a matter of debate: while some authors consider them as driven by lexical co-occurrences, others emphasize the role of meaning-based connections. To test these contrastive hypotheses, we analyzed responses in a WA task in terms of their normative defining features (those describing the object denoted by the cue word). Results indicate that 72.5% of the responses had medium-to-high coincidence with such defining semantic features. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
0
15
0
5
Order By: Relevance
“…erupt-volcano), while figurative uses (e.g. erupt-violence), often found in corpora, are uncommon in WA (Thwaites 2019);  Responses to concrete noun cues in WA correspond to a high degree (72.5%) with defining semantic features of their cue (Vivas et al 2018);  Semantic aspects of cue words (e.g. verbs pertaining to weather, bodily processes, or motion) influence proportions of responses of different types (e.g.…”
Section: Mapping Word Association Findings Onto Psychological Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…erupt-volcano), while figurative uses (e.g. erupt-violence), often found in corpora, are uncommon in WA (Thwaites 2019);  Responses to concrete noun cues in WA correspond to a high degree (72.5%) with defining semantic features of their cue (Vivas et al 2018);  Semantic aspects of cue words (e.g. verbs pertaining to weather, bodily processes, or motion) influence proportions of responses of different types (e.g.…”
Section: Mapping Word Association Findings Onto Psychological Constructsmentioning
confidence: 99%
“…erupt-violence ), often found in corpora, are uncommon in WA (Thwaites, 2019). Responses to concrete noun cues in WA correspond to a high degree (72.5%) with defining semantic features of their cue (Vivas, Manoiloff, Garcia, Lizarralde, & Vivas, 2018). Semantic aspects of cue words (e.g.…”
Section: Key Notions For Future Wa Researchmentioning
confidence: 99%
“…Language constraints become one of the obstacles in the representation of structural knowledge. As shown in the questionnaire 56% of the participant confirmed that it was not easy to construct the wording in English language, or in other words, the problem occurs in relating between semantic and lexical associations (Vivas et al, 2019). The construction of this meaning is very significant, especially in English language learners as a foreign language in developing countries (Ingerpuu-Rummel, 2018).…”
Section: Factors Affecting the Structural Knowledgementioning
confidence: 97%
“…Ця ланка в ланцюгу між двома світами супроводжується культурними уявленнями про предмети і явища культурного світу, властиві певному мовленнєвому колективу загалом та індивідуальному носію мови зокрема (Венжинович, 2006). Семантичні зв'язки через асоціації респондентів констатують представники сучасних наукових досліджень (Vivas, Manoiloff, García, Lizarralde & Vivas, 2019).…”
Section: результати та дискусіїunclassified